C++ Programming tutoring simulation "CyberCPP" / Muhammad Nor Mahat - Muhammad Nor, Mahat (2005)
Knowledge would give us an edge to success. However, the process to achieve such knowledge needs a lot of effort. Nevertheless, the information itself somehow should also be easy to be absorbed by people. It needs techniques and strategies to make sure this to happen so that those people can utilize and benefit from it CyberCPP is a web-based interactive multimedia learning package system developed for anyone who is interested in learning C++ programming. CyberCPP is an attempt to tackle this situation by using the multimedia elements. It is designed to create an information rich environment of education resources, which could be obtained from any place at any time. User also would found out that it would be easy to learn C++ programming language because CyberCPP would show how to understand the flow of the language. Other than that, user would found that CyberCPP is full with lessons, exercises and quizzes which give them more strong foundation towards C++. CyberCPP used Rapid Application Development Model for the development process to ensure the best quality would be achieved. The development tools include Macromedia Dreamweaver MX, Macromedia Flash MX, JavaScript, ActionScript, ASP.NET and Microsoft Access XP. It is hoped that CyberCPP would give user a new way of learning C++ programming language and be able to promote users' interest towards C++, which is powerful and useful.